Emerging Bioelectronics for Brain Organoid Electrophysiology - Tasnim, Kazi; Liu, Jia (Journal of molecular biology, 2022)
[Display omitted] •Brief introduction of the development, generation, and applications of human brain organoids, and conventional methods used for characterizing the morphological, genetic, and electrical properties of brain organoids.•Highlight of the need for characterizing electrophysiological properties of brain organoids in a minimally invasive manner.•Introduction of recent advances in the multi-electrode array (MEA), 3D bioelectronics, and flexible bioelectronics and their applications in brain organoid electrophysiological measurement.•Introduction of the recently developed cyborg organoids platform as an emerging tool for the long-term stably 3D characterization of the brain organoids electrophysiology at high spatiotemporal resolution.•Perspectives of new technologies that could achieve the high-throughput, cell-type-specific and multimodal characterizations from the same brain organoids. Human brain organoids are generated from three-dimensional (3D) cultures of human induced pluripotent stem cells and embryonic stem cells, which partially replicate the development and complexity of the human brain. Many methods have been used to characterize the structural and molecular phenotypes of human brain organoids. Further understanding the electrophysiological phenotypes of brain organoids requires advanced electrophysiological measurement technologies to achieve long-term stable 3D recording over the time course of the organoid development with single-cell, millisecond spatiotemporal resolution. In this review, first, we briefly introduce the development, generation, and applications of human brain organoids. We then discuss the conventional methods used for characterizing the morphological, genetic, and electrical properties of brain organoids. Next, we highlight the need for characterizing electrophysiological properties of brain organoids in a minimally invasive manner. In particular, we discuss recent advances in the multi-electrode array (MEA), 3D bioelectronics, and flexible bioelectronics and their applications in brain organoid electrophysiological measurement. In addition, we introduce the recently developed cyborg organoids platform as an emerging tool for the long-term stable 3D characterization of the brain organoids electrophysiology at high spatiotemporal resolution. Finally, we discuss the perspectives of new technologies that could achieve the high-throughput, multimodal characterizations from the same brain organoids.